THE STATUS OF STUDYING PHRASEOLOGISMS IN ENGLISH AND UZBEK LANGUAGES (Universal International Scientific Journal, 2026)
This article analyzes the history, stages of development, and current state ofphraseological units in English and Uzbek linguistics. The specific features of phraseologisms inlanguages belonging to two different families and the views of scholars who have studied them arecomparatively studied
Keywords: phraseology; phraseological units; comparative analysis